to do this problem i substituted the two equations into the x + y - dy/dt = 1. and solved it for dy/dt, the problem checked out. but i couldnt do that with the other side?? any thoughts?
verify that the pair of functions x = t + e^t , y = te^t is a solution to the system of differential equations.
x + y - dy/dt = 1 , x - dx/dt = t - 1.
ok so i was able to prove that the pair of functions were solutions to the x + y - dy/dt = 1.
but i couldnt prove they were solutions to the equation on the right, x - dx/dt = t - 1.
any thoughts? thanks in advance.